Housing and Human Settlements in a World of Change. - (:unkn) unknown (transcript, 2020)
The challenge of housing is increasingly recognised in international policy discussions in connection to the processes of migration, climate change, and economic globalisation. This book addresses the challenges of housing and emerging solutions along the lines of three major dynamics: migration, climate change, and neo-liberalism. It explores the outcomes of neo-liberal »enabling« ideas, responses to extreme climate events with different housing approaches, and how the dynamics of migration reshape the urban housing provision in a changing world. The aim is to contextualise the theoretical discourses by reflecting on the case study context of the eleven papers published in this book.
Keywords: Wohnen; Habitat; Entwicklungsland; Landflucht; Binnenwanderung; Klimawandel; Arbeitsmigration; Wohnungspolitik; Wohnungsnot; Armut; Informeller Wohnungsbau; Neoliberalismus